Myth, ritual and the oral - Goody, Jack (Cambridge University Press, 2010)
In Myth, Ritual and the Oral Jack Goody, one of the world's most distinguished anthropologists, returns to the related themes of myth, orality and literacy, subjects that have long been a touchstone in anthropological thinking. Combining classic papers with recent unpublished work, this volume brings together some of the most important essays written on these themes in the past half century, representative of a lifetime of critical engagement and research. In characteristically clear and accessible style, Jack Goody addresses fundamental conceptual schemes underpinning modern anthropology, providing potent critiques of current theoretical trends. Drawing upon his highly influential work on the LoDagaa myth of the Bagre, Goody challenges structuralist and functionalist interpretations of oral 'literature', stressing the issues of variation, imagination and creativity, and the problems of methodology and analysis. These insightful, and at times provocative, essays will stimulate fresh debate and prove invaluable to students and teachers of social anthropology